PENGUKURAN KEPUASAN PENGGUNA DAN PENINGKATAN LAYANAN SILADDU (Sistem Informasi Pelayanan Desa dan DataTerpadu) - Budiman, Budiman; Fajar Rodiansyah, Sandi; Abdurahman, Dede (Jurnal Mnemonic, 2018)
SILADDU or the Integrated Data Services Information System is an application to record data of the population of a village. This application is expected to help village officials in administering the settlement. In addition, the application is expected to become the reference in government programs such as direct assistance from the government in providing information about who will be given help, because this application helps classify the population data based on the level of economic ability, educational level, marital status, age, gender and others. This application is relatively new so attracted me as a researcher to examine the level of user satisfaction. Thus the researchers conducted this study in order to become one of the source application developers have to pay attention to the satisfaction of his application.